Et tu Mucor? (Nepalese Journal of Ophthalmology, 2021)
Introduction: Recently, the Indian subcontinent has been hard hit by the second wave of COVID-19. Along with it, the region has become a hot spot for mucormycosis infection in patients with COVID-19.  The aim of this paper  is to provide a scientific overview on the status of mucormycosis in pre-COVID-19 era and on how COVID-19 could have directly or indirectly expose the hidden burden of mucormycosis globally.Materials and methods: This paper is structured as a narrative review  and is based on relevant  published literature on both COVID-19 and mucormycosis. Conclusion: Mucormycosis in the pre-COVID-19 era was almost a neglected entity. It was because  the risk factors for both - More severe COVID-19 infections and Mucormycosis are almost similar – COVID-19  might have helped to expose the true magnitude of the mucormycosis and flagging it as a major public health concern requiring a revisit by medical science.